1998
DOI: 10.1079/bjn19980061
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine metabolism in the gastrointestinal tract of the rat assessed by the relative activities of glutaminase (EC 3.5.1.2) and glutamine synthetase (EC 6.3.1.2)

Abstract: The activities of the two key enzymes involved in glutamine metabolism, glutaminase (EC 3.5.1.2) and glutamine synthetase (EC 6.3.1.2), have been measured in the various tissues of the gastrointestinal (GI) tract of the rat, from the mouth to the rectum. Glutaminase activity was particularly high in the mucosa of the small intestine, where its activity accounted for more than 80 % of the total activity of the GI tract. In contrast, the mouth and oesophagus had very low activities, accounting for less than 2 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 41 publications
3
29
1
1
Order By: Relevance
“…However, and similarly to what was observed in rat (James et al, 1998), gilthead sea bream presented a two-fold lower GSase / GlNase ratio in the intestine than in the liver, which suggests a high dependency of the intestine on an external Gln supply. This is also supported by the higher GlNase activity in the …”
Section: Discussionsupporting
confidence: 80%
“…However, and similarly to what was observed in rat (James et al, 1998), gilthead sea bream presented a two-fold lower GSase / GlNase ratio in the intestine than in the liver, which suggests a high dependency of the intestine on an external Gln supply. This is also supported by the higher GlNase activity in the …”
Section: Discussionsupporting
confidence: 80%
“…Oral bolus glutamine treatment significantly raised glutamine levels in plasma (Table 3). Levels of glutamate were elevated in colonic mucosa, as would be expected due to the high glutaminase activity in mucosal tissue (32,33). Oral bolus glutamine treatment did not affect the levels of glutamine or glutamate in the tumor.…”
Section: Resultsmentioning
confidence: 58%
“…30,31 Other mechanisms of glutamine action could be related to anabolic properties 2,6,9 or its analgesic and anti-inflammatory properties. 32 Studies in man have shown that low-dose oral glutamine significantly increases plasma bicarbonate, the major buffer of acid in the blood, as well as growth hormone.…”
Section: Discussionmentioning
confidence: 99%